Potensi Retribusi Parkir Kawasan Plaza Pangkalpinang – Bangka Trade Center terhadap Pendapatan Asli Daerah Kota Pangkalpinang - Safitri, Revy; Yofianti, Desy (Universitas Islam 45, 2021)
The use of roadsides as parking spaces in the Pangkalpinang Plaza - Bangka Trade Center Area, if managed optimally, can be a source of Regional Original Income for Pangkalpinang City. The determination of this area as one of the on-street parking zones has the potential to be a significant contributor to parking fees revenue in Pangkalpinang City. Therefore, a study is needed to know the potential for parking fees in the Pangkalpinang Plaza - Bangka Trade Center Area to the Original Regional Income of Pangkalpinang City. The potential for parking fees revenue in Pangkalpinang City is analyzed based on three types of tariff conditions, consist of official tariffs, current tariffs, and adjustment tariffs. The results of the analysis of the potential parking fees for on-street parking in the Pangkalpinang Plaza - Bangka Trade Center Area shows that on-street parking fees revenue in this area has greats potential for the Original Regional Income of Pangkalpinang City. However, the management of the retribution receipt has not been carried out optimally, so that the revenue from this source is still low. Besides, coordination and transparency in managing parking fees also need to be improved. Furthermore, this research is expected to be used as a consideration for the government in making parking policies to optimize the receipt of parking fees in this area.